1970
DOI: 10.4314/ejhs.v28i6.12
|View full text |Cite
|
Sign up to set email alerts
|

Physicians’ Knowledge and Attitude towards Mental Health in Saudi Arabia

Abstract: BACKGROUND: Physicians working in Saudi Arabia belong to different countries and may have differences in knowledge and attitude towards psychiatry. We evaluated non psychiatric physician’s knowledge and attitude towards psychiatric disorders, such as anxiety and depression, in the Kingdom of Saudi Arabia.METHODS: A descriptive cross-sectional study design was used. The current knowledge and attitude towards anxiety and depression of physicians were determined by using a questionnaire. We distributed 180 study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 13 publications
3
40
0
2
Order By: Relevance
“…Similar findings have been reported in other studies. 64,65,66 In contrast, some studies have reported low levels of mental illness knowledge amongst doctors, 15,19,67,68 particularly in those who had little or no formal psychiatric training. It would appear that non-psychiatric doctors are, at the very least, comfortable in diagnosing common mental illnesses such as depression but feel less confident in being able to treat mentally ill patients effectively.…”
Section: Knowledge Of Mental Illnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar findings have been reported in other studies. 64,65,66 In contrast, some studies have reported low levels of mental illness knowledge amongst doctors, 15,19,67,68 particularly in those who had little or no formal psychiatric training. It would appear that non-psychiatric doctors are, at the very least, comfortable in diagnosing common mental illnesses such as depression but feel less confident in being able to treat mentally ill patients effectively.…”
Section: Knowledge Of Mental Illnessmentioning
confidence: 99%
“…Significant associations were made in other studies. Younger age, 66 engagement in mental health training not long before participation in a research study, 69,70 as well as being a family physician (compared to GPs or other specialists) 64 are associated with better diagnostic and practical knowledge. Aruna et al 20 found that the level of knowledge in undergraduate medical students increased with progressive years of study, such that students in their final years had better mental health literacy than those in their first year of study.…”
Section: Sociodemographic Variables Associated With Knowledge Of Mental Illnessmentioning
confidence: 99%
“…Regarding the precision and confidence estimate, all the evidence derived from observational studies is classified as low quality. The risk of bias assessment among articles showed that 5 articles scored >7, [18][19][20]22,24 which is considered as high quality, while the other 2 articles scored between 5 and 7 (moderate quality) 21,23 (Table 2). A high degree of inconsistency was noticed in the review as the study populations varied greatly.…”
Section: Quality Of Evidencementioning
confidence: 99%
“…Istraživanja o stigmatizaciji mentalnih poremećaja provode se u različitim populacijama, najčešće u općoj populaciji, među mentalno bolesnim osobama i njihovim obiteljima te među zdravstvenim radnicima i stručnjacima (14,(16)(17)(18)(19). Brojna su istraživanja pokazala da je stigmatizacija pojedinaca s mentalnim poremećajima vrlo raširena i da mnoge sociokulturne zajednice imaju predrasude, tj.…”
Section: Introductionunclassified
“…Studies on stigmatization of mental disorders have been conducted in various populations, most commonly in the general population, among individuals with mental illness and their families, and among health professionals and experts (14,(16)(17)(18)(19). Numerous studies have shown that stigmatization of individuals with mental disorders is very widespread and that many socio-cultural communities have prejudices and negative attitudes toward the mentally ill (20), and that stigmatization of people with mental disorders is present in different cultures (21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%